Physician performance feedback in a Canadian academic center. Issue 4 (2nd October 2017) - Garvin, Dennis; Worthington, James; McGuire, Shaun; Burgetz, Stephanie; Forster, Alan J.; Patey, Andrea; Gerin-Lajoie, Caroline; Turnbull, Jeffrey; Roth, Virginia
Abstract : Purpose: This paper aims at the implementation and early evaluation of a comprehensive, formative annual physician performance feedback process in a large academic health-care organization. Design/methodology/approach: A mixed methods approach was used to introduce a formative feedback process to provide physicians with comprehensive feedback on performance and to support professional development. This initiative responded to organization-wide engagement surveys through which physicians identified effective performance feedback as a priority. In 2013, physicians primarily affiliated with the organization participated in a performance feedback process, and physician satisfaction and participant perceptions were explored through participant survey responses and physician leader focus groups. Training was required for physician leaders prior to conducting performance feedback discussions. Findings: This process was completed by 98 per cent of eligible physicians, and 30 per cent completed an evaluation survey. While physicians endorsed the concept of a formative feedback process, process improvement opportunities were identified. Qualitative analysis revealed the following process improvement themes: simplify the tool, ensure leaders follow process, eliminate redundancies in data collection (through academic or licensing requirements) and provide objective quality metrics. Following physician leader training on performance feedback, 98 per cent of leaders who completed an evaluation questionnaire agreed or strongly agreed that the performance feedback process was useful and that training objectives were met. Originality/value: This paper introduces a physician performance feedback model, leadership training approach and first-year implementation outcomes. The results of this study will be useful to health administrators and physician leaders interested in implementing physician performance feedback or improving physician engagement.